1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Prove identity sec^-1(x) = cos^-1(1/x)

  1. Apr 8, 2013 #1
    1. The problem statement, all variables and given/known data

    Find and prove the identity sec^-1(x) in terms of cos^-1(arg) (Note that 1/cos^-1(x) is not equal to sec^-1(x).

    2. Relevant equations

    None.

    3. The attempt at a solution

    sec(sec^-1(x)) = x

    1/cos(sec^-1(x)) = x

    1/cos(cos^-1(x)) = 1/x

    1/cos(cos^-1(1/x)) = 1/1/x = x

    cos^-1(1/x) = sec^-1(x).

    Is this correct?
     
  2. jcsd
  3. Apr 8, 2013 #2

    Mark44

    Staff: Mentor

    How do you justify the previous step?
     
  4. Apr 8, 2013 #3

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    The fundamental problem with try to prove "[itex]sec^{-1}(x)= cos^{-1}(1/x)[/itex]" is that it is NOT true! This is NOT an identity. For example, if [itex]x= \pi/4[/itex] [itex]sec^{-1}(x)= \sqrt{2}/2[/itex] while [itex]1/x= 4/\pi[/itex], cos(1/x)= 3.41, approximately.
     
  5. Apr 8, 2013 #4

    SammyS

    User Avatar
    Staff Emeritus
    Science Advisor
    Homework Helper
    Gold Member

    [itex]\displaystyle \sec(\pi/4)=\sqrt{2}\ [/itex]

    [itex]\displaystyle \sec^{-1}(\pi/4)\ [/itex] is undefined, since [itex]\displaystyle\ \ \pi/4<1\ .[/itex]
     
  6. Apr 8, 2013 #5

    SammyS

    User Avatar
    Staff Emeritus
    Science Advisor
    Homework Helper
    Gold Member

    I would be inclined to write sec-1(x) as [itex]\displaystyle \ \sec^{-1}\left(\frac{1}{1/x}\right)\,,\ [/itex] then use the identity, cos(cos-1(u) = u , for the denominator.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted



Similar Discussions: Prove identity sec^-1(x) = cos^-1(1/x)
  1. How to prove -(-x)=x (Replies: 21)

  2. Sin(x) + cos(x) (Replies: 4)

Loading...